2022
DOI: 10.1002/aelm.202201095
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin, Breathable, Permeable, and Skin‐Adhesive Charge Storage Electronic Tattoos Based on Biopolymer Nanofibers and Carbon Nanotubes

Abstract: Ultrathin, breathable, and skin‐compatible epidermal electronics are attractive for wearable and implantable healthcare and biomedical applications. However, materializing and integrating all electronic components on ultrathin platforms is still challenging. Here, a charge‐storing electronic tattoo (E‐tattoo) device with ultrathin, breathable, and skin‐compatible properties is reported. Silk protein nanofibers (SNFs) and carbon nanotubes (CNTs) form the top and bottom electrodes that sandwich the intermediate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 50 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…Compared to batteries, supercapacitors exhibit much faster charging and discharging speed and longer life cycles. , Luan et al reported a supercapacitor with PEDOT:PSS decorated SWCNT film serving as positive and negative electrodes. The device has a low thickness of only ∼1 μm but a high-power density of 332 kW·kg –1 .…”
Section: E-tattoos For Energy Harvesting and Storagementioning
confidence: 99%
“…Compared to batteries, supercapacitors exhibit much faster charging and discharging speed and longer life cycles. , Luan et al reported a supercapacitor with PEDOT:PSS decorated SWCNT film serving as positive and negative electrodes. The device has a low thickness of only ∼1 μm but a high-power density of 332 kW·kg –1 .…”
Section: E-tattoos For Energy Harvesting and Storagementioning
confidence: 99%
“…Fabrication of uorescent silk textiles can be accomplished through several means. For example, a dye can be added to a silk solution, which can then be electrospun to form nano bers [32][33][34] . Else ways, inorganic nanoparticles (quantum dots) when embedded in silk bers can facilitate colored silk materials 35 .…”
Section: Introductionmentioning
confidence: 99%